Overview of Geographical Location of Puskesmas and Level of Nurses' Knowledge in Tsunami Disaster Risk Mitigation Preparedness in Banda Aceh - Afdhal, Afdhal; Rimadeni, Yeni; Hayati, Wirda; Jamni, Teuku; Desiana, Desiana; Munazar, Munazar (Journal Keperawatan, 2024)
Background: The 2004 Tsunami in Aceh caused infrastructure damage, thousands of deaths, and significant economic and health crises. Health facilities such as Community Health Centers (Puskesmas) which are the main health facilities in saving patients' lives were destroyed. To overcome this impact, health infrastructure must be rebuilt with earthquake-resistant building structures using certain materials and systems to withstand vertical and lateral loads that occur during earthquakes. In addition, nurses as primary health workers must have sufficient knowledge and skills to prevent loss of life if the disaster occurs through disaster mitigation preparedness. Purpose:  To identify the geographical distribution of Puskesmas locations in Banda Aceh City based on the level of tsunami risk and assess the level of knowledge of nurses' preparedness in facing disaster situations. Methods: Descriptive research type with spatial analysis method was used in this study. The data used included topographic maps, tsunami risk maps, and Puskesmas locations, which were analyzed using ArcGIS software. For nurses' knowledge level data, the population used was the entire number of nurses at the Banda Aceh City Puskesmas and used a total sampling technique which resulted in a sample of 87 nurses. Results: The study showed that 7 out of 11 Puskesmas (63.6%) in Banda Aceh were in the moderate to high tsunami risk zone. The level of knowledge of nurses regarding tsunami disaster preparedness was mostly good, namely 65 people (75%). Conclusion: Almost half of the Puskesmas in Banda Aceh are geographically located in the high tsunami risk zone category and the level of knowledge of community health center nurses regarding tsunami disaster preparedness is mostly good.